Arterial Calcification and Its Association With Stroke: Implication of Risk, Prognosis, Treatment Response, and Prevention - Wang, Xiang; Chen, Xinghang; Chen, Zhuohui; Zhang, Mengqi (Frontiers in Cellular Neuroscience, 2022)
Stroke is a leading cause of death worldwide. Vascular calcification (VC), defined as deposition of calcium-phosphate complexes in the vessels, is considered as the characteristic of vascular aging. Calcifications at different vessel layers have different implications. Intimal calcification is closely related to atherosclerosis and affects plaque stability, while medial calcification can cause arterial stiffening and reduce compliance. Accumulating evidences suggest that arterial calcifications, including calcifications in intracranial artery, coronary artery and carotid artery, are associated with the risk, prognosis and therapeutic effects of stroke. VC can not only serve as a marker of atherosclerosis, but cause cerebral hemodynamic impairment. In addition, calcifications in large arteries are associated with cerebral small vessel disease. In this review, we summarize the findings of recent published studies focusing on the relationship between large artery calcification and the risk, prognosis, therapeutic effects and prevention of stroke and also discuss possible mechanisms behind those associations.